2017
DOI: 10.1001/journalofethics.2017.19.11.medu1-1711
|View full text |Cite
|
Sign up to set email alerts
|

Co-Creating an Expansive Health Care Learning System

Abstract: How should practices of co-creation be integrated into health professions education? Although co-creation permits a variety of interpretations, we argue that realizing a transformative vision of cocreation-one that invites professionals to genuinely reconsider the purposes, relationships, norms, and priorities of health care systems through new forms of collaborative thought and practice-will require radically rethinking existing approaches to professional education. The meaningful enactment of co-creative rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Discussion groups are an effective way of listening to what children have to say [ 66 ] by integrating their voices with those of teachers or family members [ 19 , 59 , 60 ]. Other studies have involved municipalities [ 40 ] or expert professionals [ 67 ]. We included all of these voices in our research, which also revealed the usefulness of the indirect observation of preschoolers and teachers as an effective strategy to assess classroom implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion groups are an effective way of listening to what children have to say [ 66 ] by integrating their voices with those of teachers or family members [ 19 , 59 , 60 ]. Other studies have involved municipalities [ 40 ] or expert professionals [ 67 ]. We included all of these voices in our research, which also revealed the usefulness of the indirect observation of preschoolers and teachers as an effective strategy to assess classroom implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Providing opportunities for patients to participate in the design and delivery of health professional education is one of the key requirements for patient-centred care (Ogden et al, 2017). Cribb et al (2017) identify that co-creation with patients in medical education is an opportunity for medical schools to role model underpinning principles of patientcentred care and contribute to transformative change in healthcare. In keeping with this is the meta-narrative of "democratization of health professions education" identified by Rowland et al (2019), whereby "expert and engaged" patients are involved in medical education.…”
Section: Discussionmentioning
confidence: 99%
“…For health professional learners, shared decision making with patients, interprofessional teams, and other key stakeholders following graduation has been argued to be a critical skill needed for patient-centered care (Cribb, 2017). Cribb (2017) argued that for medical graduates to be prepared to make joint decisions about how to solve healthcare problems with key stakeholders after graduation it is important to embed opportunities to learn how to co-create during their education.…”
Section: Background 1| the Problemmentioning
confidence: 99%
“…The term co-creation is used in a variety of ways to describe shared decision making with different parties. Co-creation in the healthcare context has involved patients, healthcare professionals, and other key stakeholders in collaborative problem solving (Cribb, 2017). Working with others who are more knowledgeable than the learner in an interactive way is theorized to enhance learner development (Vygotskiĭ, 1978).…”
Section: Background 1| the Problemmentioning
confidence: 99%